2023
DOI: 10.1186/s10194-023-01554-9
|View full text |Cite
|
Sign up to set email alerts
|

The HARDSHIP databases: a forthcoming free good from the Global Campaign against Headache

Abstract: In order to pursue its purpose of reducing the global burden of headache, the Global Campaign against Headache has gathered data on headache-attributed burden from countries worldwide. These data, from the individual participants in adult population-based studies and child and adolescent schools-based studies, are being collated in two databases, which will be powerful resources for research and teaching and rich information sources for health policy.Here we briefly describe the structure and content of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Given that, in studies that have reported both, they are approximately equal in prevalence [ 21 ], should they be considered equal in their contributions to burden – including YLD estimates? There are empirical data that will answer this question [ 22 ] for future GBD iterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that, in studies that have reported both, they are approximately equal in prevalence [ 21 ], should they be considered equal in their contributions to burden – including YLD estimates? There are empirical data that will answer this question [ 22 ] for future GBD iterations.…”
mentioning
confidence: 99%
“…Are the DWs fair in their relative weighting of migraine and TTH? There are empirical data that will answer this question also [ 22 ].…”
mentioning
confidence: 99%